The Effect Of Using Teaching Aids For Forehand Spring On Floor Exercises In Men's Artistic Gymnastics - Abdulwahed Lazem, Ali (Journal of Physical Education, 2018)
The Effect Of Using Teaching Aids For Forehand Spring On Floor Exercises In Men's Artistic GymnasticsThe research aimed at identifying the effect of using teaching aids for forehand spring on floor exercises in Men's artistic Gymnastics. The researcher hypothesized using teaching aids positively affect forehand spring on floor exercises. The researcher used the experimental method. The subjects were 40 male students. The researcher used a sponge cylinder roll and a spring mat. Two pilot studies were conducted followed by 24 training session for three months for two experimental groups and one controlling group. The results showed that experimental group students have fun using the teaching aids compared to the controlling group. The teaching aid made the center of gravity higher and helped students in performing correctly. The researcher recommended making cylinder roll with sizes to suit the students' heights and weights and providing coaches in youth clubs as well as physical education teachers for their positive effect on learning.Keywords: forehand spring, teaching aid, men's artistic gymnastics.